Arene CH Amination at Nickel in Terphenyl–Diphosphine Complexes with Labile Metal–Arene Interactions. Issue 48 (14th October 2013) - Herbert, David E.; Lara, Nadia C.; Agapie, Theodor
Abstract The meta‐terphenyl diphosphine, m‐P2, 1, was utilized to support Ni centers in the oxidation states 0, I, and II. A series of complexes bearing different substituents or ligands at Ni was prepared to investigate the dependence of metal–arene interactions on oxidation state and substitution at the metal center. Complex (m‐P2)Ni (2) shows strong Ni0–arene interactions involving the central arene ring of the terphenyl ligand both in solution and the solid state. These interactions are significantly less pronounced in Ni0 complexes bearing L‐type ligands (2‐L: L=CH3CN, CO, Ph2CN2), NiIX complexes (3‐X: X=Cl, BF4, N3, N3B(C6F5)3), and [(m‐P2)NiIICl2] (4). Complex 2 reacts with substrates, such as diphenyldiazoalkane, sulfur ylides (Ph2SCH2), organoazides (RN3: R=para‐C6H4OMe, para‐C6H4CF3, 1‐adamantyl), and N2O with the locus of observed reactivity dependent on the nature of the substrate. These reactions led to isolation of an η1‐diphenyldiazoalkane adduct (2‐Ph2CN2), methylidene insertion into a NiP bond followed by rearrangement of a nickel‐bound phosphorus ylide (5) to a benzylphosphine (6), Staudinger oxidation of the phosphine arms, and metal‐mediated nitrene insertion into an arene CH bond of 1, all derived from the same compound (2). Hydrogen‐atom abstraction from a NiI–amide (9) and the resulting nitrene transfer supports the viability of Ni–imide intermediates in the reaction of 1 with 1‐azido‐arenes.